The Effect of Dietary Protein Levels and Lysine Supplementation on Femur Strength in 12-Week-Old Indonesian Indigenous Chickens - Rizkuna, Akhmat; Fatmarischa, Novemia; Widiarta, I Putu Gede Didik; Aldiyanti, Amani (Buletin Peternakan Tropis, 2024)
This study aimed to evaluate the different levels of dietary protein and lysine supplementation on femur bone strength of Indonesian indigenous chickens at 12 weeks of age. The experimental materials used were DOC, without sex differentiation, reared up to 12 weeks of age. A completely randomized design (CRD) with a 2 × 3 factorial arrangement was used, with each treatment having four replicates and 10 chickens per experimental unit. The treatments applied were: P1L1 (17% protein + 0.6% lysine), P1L2 (17% protein + 0.7% lysine), P1L3 (17% protein + 0.8% lysine), P2L1 (14% protein + 0.6% lysine), P2L2 (14% protein + 0.7% lysine), and P2L3 (14% protein + 0.8% lysine). The experimental period started from the first day of observation to 12 weeks. Measured parameter: The main measured parameter was the femur bone strength after 12 weeks using an Electric Tensile Tester (Hun Ta Instruments CO. LTD, HT 8346). Also, histological examination of femur bones was conducted through a Scanning Electron Microscope-SEM at 100x. Data were subjected to ANOVA, and when there was a significant difference, Duncan's Multiple Range Test was conducted at a 5% significance level. No significant interaction was recorded between protein and lysine levels on femur bone strength at 12 weeks because P > 0.05. Conclusively, therefore, both dietary protein levels and lysine supplementation have no significant effect on bone strength in the finisher phase of growth.